Actualization of Pancasila Justice Values In Regarding Wage Regulations In Realizing Social Welfare - Irham Rahman; Restu Adi Putra; Dominikus Rato; Ahmad Basarah (Journal of Law, Politic and Humanities, 2024)
Indonesia is a country of law and upholds the values ??of justice, as justice is outlined in the fifth principle, namely social justice for all Indonesian people. Apart from that, the state also plays a role in improving the welfare of the people, namely ensuring that people get decent work and wages through regulations regarding wages. The latest regulations regarding wages are contained in Government Regulation (PP) No.51 of 2023 concerning Amendments to PP No.36 of 2021 concerning Wages. The problem is that the values ??of justice and existing regulations often conflict and these regulations do not even have justice values ??in accordance with the character of Pancasila. So the problem is formulated whether the values ??of justice have been actualized in wage regulations in Indonesia. This type of research uses a normative juridical research method, namely studying norms through literature and a research approach using a statutory approach, a conceptual approach and a historical approach. The research results show that based on the emergence of new regulations, namely Government Regulation (PP) No. 51 of 2023 concerning Amendments to PP No. 36 of 2021 concerning Wages, there are several changes in determining minimum wages in each region and it is hoped that these changes will be able to actualize the values ??of social justice for all Indonesian people.